2011
DOI: 10.3738/1982.2278.471
|View full text |Cite
|
Sign up to set email alerts
|

Perdas Visíveis Na Colheita Mecanizada De Cana Crua Sob Duas Velocidades De Deslocamento Da Colhedora

Abstract: RESUMO:O objetivo deste experimento foi estudar as perdas visíveis que ocorrem na cultura da cana-deaçúcar crua durante a colheita mecanizada sob duas velocidades de deslocamento da colhedora. O trabalho foi realizado na cidade de Barretos em julho de 2009. A colhedora utilizada foi a John Deer modelo 3510, onde no tratamento 1 ficou ajustada com pressão de corte de base de 1070 Psi e pressão do exaustor de 1050 Psi e velocidade de 8 km h -1 e para o tratamento 2 pressão de corte de base de 950 Psi e pressão d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
1
2
0
3
Order By: Relevance
“…These data observed for harvester efficiency in treatment A ( Figure 5 and Table 1), were close to the work conducted by Segato and Daher (2011), who evaluated the efficiency of sugarcane harvesters without using technologies such as GPS and RTK, and found losses of 10% of the final raw material harvested, a fact considered by the authors Brunini e Petrucci, v.12, n.43, p.79-88, Dourados, 2019 as a concern for the sector because the producers end up having a deficit in the order of millions of dollars per year. This can be avoided by using technologies linked to the GPS and RTK (autopilot) tools instrumented in agricultural machinery and equipment for the production of sugarcane.…”
Section: Resultssupporting
confidence: 88%
“…These data observed for harvester efficiency in treatment A ( Figure 5 and Table 1), were close to the work conducted by Segato and Daher (2011), who evaluated the efficiency of sugarcane harvesters without using technologies such as GPS and RTK, and found losses of 10% of the final raw material harvested, a fact considered by the authors Brunini e Petrucci, v.12, n.43, p.79-88, Dourados, 2019 as a concern for the sector because the producers end up having a deficit in the order of millions of dollars per year. This can be avoided by using technologies linked to the GPS and RTK (autopilot) tools instrumented in agricultural machinery and equipment for the production of sugarcane.…”
Section: Resultssupporting
confidence: 88%
“…Similarly, Segato et al (2011), when verifying the influence of increasing the sugarcane harvester's speed on plant losses, concluded that there is a relationship between these factors.…”
Section: Resultsmentioning
confidence: 99%
“…Em experimentos realizados por Segato & Daher (2011), com duas velocidades de trabalho (8 e 6,5 a 7 km h -1 ), foi observado que os tratamentos não apresentaram diferenças significativas para a perda de tolete. Os mesmos autores chamam a atenção, relatando que esse tipo de perda pode ser totalmente influenciado pelo sincronismo entre operador da colhedora e operador do trator transbordo, e também pelo excesso de material adicionado dentro do cesto do transbordo acoplado ao trator, que ao se locomover pelo terreno pode perder toletes ao longo da linha.…”
Section: Fontes De Variaçãounclassified
“…Segundo Salvi (2006), a velocidade excessiva de deslocamento na colheita pode influenciar a perda tipo pedaço. Segato & Daher (2011) observaram que não houve diferença significativa para a perda tipo pedaço quando se avaliaram as velocidades de 7,0 e 8,0 km h -1 , corroborando os resultados do presente trabalho.…”
Section: Fontes De Variaçãounclassified